2020
DOI: 10.1039/d0nr05060a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced charge storage of nanometric ζ-V2O5 in Mg electrolytes

Abstract: V2O5 is of interest as a Mg intercalation electrode material for Mg batteries, both in its thermodynamically stable layered polymorph (α-V2O5) and in its metastable tunnel structure (ζ-V2O5). However, such...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
(69 reference statements)
0
14
0
Order By: Relevance
“…To-date, the only vanadium oxides with verified Mg intercalation in dry electrolytes are layered α-V 2 O 5 , layered V 4 Nb 18 O 55 , tunnel ζ-V 2 O 5 , , and, again, spinel MgV 2 O 4 , but only at elevated temperatures (50 or 110 °C). , Of these, the report of α-V 2 O 5 is arguably the most striking, with a high capacity of 300 mA h g –1 at 110 °C confirmed by elemental, redox, and structural characterization (Figure ). Unfortunately, a Mg metal battery made using the α-V 2 O 5 as cathode experienced rapid capacity decay, reflecting an ongoing problem of insufficient electrolyte stability and parasitic reactions at both electrodes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To-date, the only vanadium oxides with verified Mg intercalation in dry electrolytes are layered α-V 2 O 5 , layered V 4 Nb 18 O 55 , tunnel ζ-V 2 O 5 , , and, again, spinel MgV 2 O 4 , but only at elevated temperatures (50 or 110 °C). , Of these, the report of α-V 2 O 5 is arguably the most striking, with a high capacity of 300 mA h g –1 at 110 °C confirmed by elemental, redox, and structural characterization (Figure ). Unfortunately, a Mg metal battery made using the α-V 2 O 5 as cathode experienced rapid capacity decay, reflecting an ongoing problem of insufficient electrolyte stability and parasitic reactions at both electrodes.…”
mentioning
confidence: 99%
“…43 Recently, Lopez et al revealed that H 2 O impurities in the electrolyte did not enhance Mg intercalation in a tunnel polymorph, ζ-V 2 O 5 , further suggesting that water inclusion in the electrolyte can easily promote competing parasitic reactions rather than enhancing Mg intercalation. 47 To-date, the only vanadium oxides with verified Mg intercalation in dry electrolytes are layered α-V 2 O 5 , 36 layered V 4 Nb 18 O 55 , 37 tunnel ζ-V 2 O 5 , 38,39 and, again, spinel MgV 2 O 4 , 62 but only at elevated temperatures (50 or 110 °C). 36,38 Of these, the report of α-V 2 O 5 is arguably the most striking, with a high capacity of 300 mA h g −1 at 110 °C confirmed by elemental, redox, and structural characterization (Figure 3).…”
mentioning
confidence: 99%
“…The greater effect of nanosizing on the first-cycle hysteresis (as opposed to later cycles) is supported by a previous investigation of ζ-V 2 O 5 : while reducing particle size from 150 nm-wide, micron-long rods to 100 nm diameter crystallites significantly reduced the firstcycle voltage hysteresis from 1.65 V to 1.15 V, the effect on the second cycle was much smaller (reduced from 1.29 V to 0.94 V). 25 Therefore, the presence of voltage hystereses >0.7 V, even at elevated temperatures (110°C) and with significantly nanosized particles, indicates that other energetic barriers contribute to Mg intercalation in V 2 O 5 . These barriers could originate from either inherent kinetics (such as Mg transfer from electrolyte to electrode) or thermodynamic factors associated with the electrochemical reactions that are not affected by particle size.…”
Section: Resultsmentioning
confidence: 98%
“…Indeed, a recent report revealed nanosizing ζ-V 2 O 5 results in reduced voltage hysteresis and increased capacity when cycled in Mgcontaining electrolytes. 25 Synthesized α-V 2 O 5 has typically formed micron-long nanorods, micron-wide nanosheets and hollow microspheres when prepared from solution without a physical scaffold. 33,[36][37][38] In contrast, α-V 2 O 5 prepared as part of a composite material has allowed for the formation of smaller, semi-spherical nanometric α-V 2 O 5 crystallites, where the composite material provided heterogeneous nucleation sites for V 2 O 5 crystallites and prevented their agglomeration and fusion.…”
Section: Introductionmentioning
confidence: 99%
“…These studies usually focus on different strategies to overcome the limited Mg ions diffusion rate in solid hosts that is caused by the strong electrostatic interactions between the diffusing Mg +2 cations and the host materials′ anions. The most common strategies rely on decreasing the diffusion length by using nanomaterials, [1,25,32–36] incorporation of water in the crystal structure, [1,6,26,27,29,30] and tuning the anionic species in the host materials framework in order to reduce the attraction forces between the diffusive Mg ions and the anions in the solid host matrix [9,37] . Nevertheless, addition of water is not practical because of its incompatibility with Mg metal anodes.…”
Section: Introductionmentioning
confidence: 99%